2019
DOI: 10.1175/jhm-d-19-0081.1
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Vertical Distribution of Precipitation in the Glacierized Upper Indus Basin Based on Multiple Datasets

Abstract: The quality and vertical distribution of precipitation are of utmost importance in hydrological modeling studies in glacierized catchments, which have been facing known challenges in the quality, distribution, and magnitude of observed as well as gridded precipitation due to complex topography. The purpose of the study is to reveal the vertical distribution of precipitation based on multiple datasets and evaluate the suitability of these datasets for hydrological applications and in the upper Indus basin (UIB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…3. The mean annual bias corrected CHIRPS precipitation for the study domain was estimated as 536 mm yr -1 which is closer to the results obtained by (Cheema and Bastiaanssen 2012;Reggiani and Rientjes 2015;Rizwan et al 2019;Shafeeque et al 2019) who suggested corrected precipitation 523, 675+100, 550 and 593 mm yr -1 respectively in UIB using various methods. The driest area is located over the South-Western part of the study domain along the Shingo and Zanskar basins followed by the upper part of Hunza, Shigar and the central part of Gilgit, while the highest precipitation values occur over the central part of Indus downstream, Astore, Shingo, and the upper part of Shyok.…”
Section: Climatology Anomalies and Precipitation Recordssupporting
confidence: 86%
“…3. The mean annual bias corrected CHIRPS precipitation for the study domain was estimated as 536 mm yr -1 which is closer to the results obtained by (Cheema and Bastiaanssen 2012;Reggiani and Rientjes 2015;Rizwan et al 2019;Shafeeque et al 2019) who suggested corrected precipitation 523, 675+100, 550 and 593 mm yr -1 respectively in UIB using various methods. The driest area is located over the South-Western part of the study domain along the Shingo and Zanskar basins followed by the upper part of Hunza, Shigar and the central part of Gilgit, while the highest precipitation values occur over the central part of Indus downstream, Astore, Shingo, and the upper part of Shyok.…”
Section: Climatology Anomalies and Precipitation Recordssupporting
confidence: 86%
“…In Pakistan, topographic diversity and complex land geography have a variable trend of precipitation change and variability. Previous studies have mentioned the elevation‐dependent precipitation variability at the seasonal scale and their respective trend due to global warming (Hanif et al ., 2013; Xu et al ., 2018; Yu et al ., 2018; Shafeeque et al ., 2019). Results of long‐term annual precipitation trends at various elevations classes (<250, 250–500, 500–1,000, 1,000–1,500, 1,500–2,000, >2,000 m) are presented in Figure 9.…”
Section: Resultsmentioning
confidence: 99%
“…The correction factors for the adjusted observed precipitation are based on the elevational distribution and hydrological balance of the region (Dahri et al 2018). The effect of elevation on the precipitation has been well demonstrated in previous studies (Immerzeel et al 2015, Shafeeque et al 2019. We will incorporate the important discussions to highlight further the effect of topography on precipitation and its role in classifying the hydrological behavior of the basin.…”
mentioning
confidence: 88%